2006
DOI: 10.1210/jc.2006-0021
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phosphorus Regulates Serum Fibroblast Growth Factor-23 Concentrations in Healthy Men

Abstract: We conclude that in healthy men, changes in dietary phosphorus within the physiological range of intakes regulate serum FGF-23 concentrations and suggest that dietary phosphorus regulation of 1,25(OH)(2)D production is mediated, at least in part, by changes in circulating FGF-23.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
288
7
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(325 citation statements)
references
References 43 publications
14
288
7
16
Order By: Relevance
“…In this study, as well as in a recently published large cohort of adults with predialysis CKD (9), circulating FGF-23 levels were already elevated in stage 2 CKD, consistent with the marked upregulation of FGF-23 expression in bone observed in patients with this degree of kidney disease (18). Although controversial (19)(20)(21), some investigators have shown that FGF-23 levels increase in response to oral phosphate loading in healthy volunteers (22) as well as in wild-type and CKD rats (23); thus, an increased, possibly intermittent, phosphate burden in the context of even mildly decreased renal function may contribute to enhanced FGF-23 secretion. Phosphate-independent mechanisms, such as subtle, subclinical elevations in PTH, may also contribute to the increase in FGF-23 levels in CKD.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, as well as in a recently published large cohort of adults with predialysis CKD (9), circulating FGF-23 levels were already elevated in stage 2 CKD, consistent with the marked upregulation of FGF-23 expression in bone observed in patients with this degree of kidney disease (18). Although controversial (19)(20)(21), some investigators have shown that FGF-23 levels increase in response to oral phosphate loading in healthy volunteers (22) as well as in wild-type and CKD rats (23); thus, an increased, possibly intermittent, phosphate burden in the context of even mildly decreased renal function may contribute to enhanced FGF-23 secretion. Phosphate-independent mechanisms, such as subtle, subclinical elevations in PTH, may also contribute to the increase in FGF-23 levels in CKD.…”
Section: Discussionsupporting
confidence: 88%
“…Epidemiologic and experimental data support FGF23 elevation as a novel risk factor for ESRD, cardiovascular disease, and mortality (2)(3)(4)(5). These findings, along with evidence that FGF23 levels increase with dietary phosphate loading and decrease with restriction (6)(7)(8), have stimulated interest in developing clinical strategies to reduce FGF23 levels in CKD.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies on FGF23 response on phosphate loading have revealed conflicting results because of differences in timing of sample collection, follow-up, and different assays used to determine FGF23 levels (2)(3)(4)(5). One study demonstrated an increase in C-terminal FGF23 (cFGF23) on phosphate loading, but it measured FGF23 only after 5 days, thereby precluding any conclusion on the time window before that (3).…”
Section: Introductionmentioning
confidence: 99%